A study of linguistic features of hotels’ names in english versus vietnamese - Phạm,Thị Hải Phượng (ĐHNN, 2016)
This thesis is designed to investigate the similarities and differences of hotels’ names in English and Vietnamese especially in terms of structural and semantic features. The investigation of 420 hotels’ names taken from Internet in English and Vietnamese (210 samples for each language) is carried out basing on both descriptive and contrastive methods. From the study’s results, the thesis gives a remarkably detailed description of structural and semantic features of hotels’ names in English and Vietnamese and points out some similarities and differences between them. The thesis also suggests some implications for teachers, learners, cross cultural communicators, hotels’ owners and advertisers as well as puts forward some suggestions for further study.
Keywords: linguistic features